A conspiracy of ravens [large type] - Morris, Gilbert (Morris, Gilbert. Lady Trent mysteries, 2009)
With the aid of her partner Dylan Tremayne, Lady Serafina Trent aims to help her neighbors, the Haydens, determine who the true heir is to their sizable estate. After some investigating, she shocks the Haydens when she reveals that the child they believed had died at birth is actually alive and living as a criminal in London's worst slum. Then the Hayden's butler is murdered and the stakes are dangerously raised. Now Lady Trent's sleuthing skills are put to the test...